A New Database of Financial Reforms - Detragiache, Enrica (IMF Working Papers; Working Paper ;, 2008)
This paper introduces a new database of financial reforms, covering 91 economies over 1973-2005. It describes the content of the database, the information sources utilized, and the coding rules used to create an index of financial reform. It also compares the database with other measures of financial liberalization, provides descriptive statistics, and discusses some possible applications. The database provides a multi-faceted measure of reform, covering seven aspects of financial sector policy. Along each dimension the database provides a graded (rather than a binary) score, and allows for reversals.